SEMIOTIC ANALYSIS OF ROLAND BARTHES ON THE COVER OF TEMPO MAGAZINE “28 JANUARY 2025 EDITION” - Nezar Ariffananda; Reni Nuraeni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to uncover the visual and ideological meanings on the cover of Tempo Magazine, January 28, 2025 edition, featuring the pair President Prabowo Subianto and Vice President Gibran Rakabuming Raka. Using Roland Barthes' semiotic approach, the analysis was conducted at three main levels: denotation, connotation, and myth. The results of the study show that the cover not only represents political figures visually, but also constructs a narrative of power that is hegemonic and ideological. At the denotative level, the visuals show Prabowo in a dominant pose and Gibran in a subordinate position. At the connotative level, gestures, expressions, clothing, and attributes such as shopping bags and background colors imply the symbolism of leadership, populism, and a hierarchical but harmonious power structure. Meanwhile, at the myth level, this cover works to naturalize power relations and government legitimacy as something natural, neutral, and undeniable. These findings emphasize that media visuals do not merely convey information, but also produce ideological meanings that influence the way the public understands contemporary political reality. Thus, visual media plays an important role in shaping opinions and reinforcing dominant discourses through complex processes of symbolic representation.